2012
DOI: 10.1155/2012/320542
|View full text |Cite
|
Sign up to set email alerts
|

The Observation of Humoral Responses after Influenza Vaccination in Patients with Rheumatoid Arthritis Treated with Japanese Oriental (Kampo) Medicine: An Observational Study

Abstract: Objective. The efficacy of influenza vaccination in patients treated with Japanese Oriental (Kampo) Medicine is unknown. The objectives of this study were to observe the efficacy of influenza vaccination in RA patients treated with Kampo. Methods. Trivalent influenza subunit vaccine was administered to 45 RA patients who had received Kampo. They were divided into 2 groups: RA patients treated without MTX (“without MTX group”) and treated with MTX (“with MTX group”). Antibody titers were measured before and 4 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Influenza vaccination did not influence activity of the underlying AIIRD in patients with RA,7 8 12 14 15 38 39 42 54 55 57 71–73 SLE,6 19 21 26 28 37 43 45–47 ANCA-associated vasculitis30 31 48 or systemic sclerosis 32 49. Adverse events of influenza vaccination in patients with AIIRD were comparable to those in HCs in most studies,7 19 21 23 30 59 65 including a meta-analysis in patients with SLE,46 In contrast, a meta-analysis including 13 studies in patients with RA concluded that local, mild adverse events occurred significantly more frequently in patients with RA 42…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Influenza vaccination did not influence activity of the underlying AIIRD in patients with RA,7 8 12 14 15 38 39 42 54 55 57 71–73 SLE,6 19 21 26 28 37 43 45–47 ANCA-associated vasculitis30 31 48 or systemic sclerosis 32 49. Adverse events of influenza vaccination in patients with AIIRD were comparable to those in HCs in most studies,7 19 21 23 30 59 65 including a meta-analysis in patients with SLE,46 In contrast, a meta-analysis including 13 studies in patients with RA concluded that local, mild adverse events occurred significantly more frequently in patients with RA 42…”
Section: Resultsmentioning
confidence: 99%
“…The influence of immunomodulating agents on influenza vaccine efficacy and immunogenicity is summarised in table 6. No influence of methotrexate (MTX) on influenza immunogenicity was found in most studies39 40 43 62 72 74 including one meta-analysis in patients with RA 75. In some, a modest reduction in immunogenicity was observed 58–60 73 76.…”
Section: Resultsmentioning
confidence: 99%